LCOS Spatial Light Modulator for Digital Holography - Wu, Weijie; Pivnenko, Mike; Chu, Daping (Photonics Letters of Poland, 2021)
Liquid crystal on silicon (LCOS) spatial light modulator (SLM) is the most widely used optical engine for digital holography. This paper aims to provide an overview of the applications of phase-only LCOS in two-dimensional (2D) holography. It begins with a brief introduction to the holography theory along with its development trajectory, followed by the fundamental operating principle of phase-only LCOS SLMs. Hardware performance of LCOS SLMs (in terms of frame rate, phase linearity and flicker) and related experimental results are presented. Finally, potential improvements and applications are discussed for futuristic holographic displays. Full Text: PDF References M. Wolfke, Physikalische Zeitschrift 21, 495 (1920). DirectLink D. Gabor, "A New Microscopic Principle", Nature 161, 777 (1948). CrossRef H. Haken, "Laser Theory", Light and Matter 5, 14 (1970). CrossRef S. Benton, "Selected Papers on Three-dimensional displays", SPIE Press (2001). DirectLink X. Liang et al, "3D holographic display with optically addressed spatial light modulator", 3DTV-CON 2009 - 3rd 3DTV-Conference (2009). CrossRef J. Chen, W. Cranton, M. Fihn, "Handbook of Visual Display Technology", Springer (2012). CrossRef D. Rogers, "The chemistry of photography: From classical to digital technologies", Royal Society of Chemistry (2007). CrossRef S. Reichelt et al, "Depth cues in human visual perception and their realization in 3D displays", Proc. SPIE 7690, 76900B (2010). CrossRef A.W. Lohmann, D. Paris, "Binary Fraunhofer Holograms, Generated by Computer", Appl. Opt. 6, 1739 (1967). CrossRef J.W. Goodman, R.W. Lawrence, "Digital Image Formation from Electronically Detected Hologtrams", Appl. Phys. Lett 17, 77 (1967). CrossRef D.C. O’Brien, R.J. Mears, and W.A. Crossland, "Dynamic holographic interconnects that use ferroelectric liquid-crystal spatial light modulators", Appl. Opt. 33, 2795, (1994). CrossRef R.W. Gerchberg, and W.O. Saxton, "A practical algorithm for the determination of phase from image and diffraction plane pictures", Optik 35, 237 (1972). DirectLink M. Ernstoff, A. Leupp, M. Little, and H. Peterson, "Liquid crystal pictorial display", Proceedings of the 1973 International Electron Devices Meeting, IEEE, 548 (1973). CrossRef W.A. Crossland, P.J. Ayliffe, and P.W. Ross, "A dyed-phase-change liquid crystal display over a MOSFET switching array", Proc SID 23, 15 (1982). DirectLink M. Tang, and J. Wu, "Optical Correlation recoginition based on LCOS", Internation Symposium on Photoelectronic Detection and Imaging 2013, Optical Storage and Display Tech., 8913 (2013). CrossRef A. Hermerschmidt, et al. Holographic optical tweezers with real-time hologram calculation using a phase-only modulating LCOS-based SLM at 1064 nm, Complex Light and Optical Forces II, International Society for Optics and Photonics, 30282 (2008). CrossRef M. Wang, et al. "LCoS SLM Study and Its Application in Wavelength Selective Switch", Photonics 4, 22 (2017). CrossRef Z. Zhang, Z. You, and D. Chu, "Fundamentals of phase-only liquid crystal on silicon (LCOS) devices", Light Sci. & Appls. 3, e213 (2014). CrossRef D. Yang, and S. Wu, Fundamentals of liquid crystal devices, 2nd edition (Wiley 2015). CrossRef B. Prince, Semiconductor memories: A handbook of design, manufacture, and application, 2nd ed. (John Wiley & Sons 1996). DirectLink J.C. Jones, Liquid crystal displays, Handbook of optoelectronics: Enabling Technologies, 2nd ed. (CRC Press 2018). DirectLink A. Ayriyan, et al. "Simulation of the Static Electric Field Effect on the Director Orientation of Nematic Liquid Crystal in the Transition State", Phys. Wave Phenom. 27, 67 (2019). CrossRef S.M. Kelly, and M. O’Neil, Liquid crystal for electro-optic applications, Handbook of advanced electronics and photonic materials and devices 7, 15 (2000). DirectLink Y. Ji, et al., "Suspected Intraoperative Anaphylaxis to Gelatin Absorbable Hemostatic Sponge", J. SID 22, 4652 (2015). CrossRef X. Chang, Solution-processed ZnO nanoparticles for optically addressed spatial light modulator and other applications, Ph.D. thesis, (University of Cambridge, Cambridge 2019) CrossRef E. Moon, et al. "Holographic head-mounted display with RGB light emitting diode light source", Opt. Express 22, 6526 (2014). CrossRef G. Aad, et al. "Study of jet shapes in inclusive jet production in pp collisions at √s=7 TeV using the ATLAS detector", Phys Rev. D 83, 052003 (2011). CrossRef M. Pivnenko, K. Li, and D. Chu, "Sub-millisecond switching of multi-level liquid crystal on silicon spatial light modulators for increased information bandwidth", Opt. Express 29, 24614 (2021). CrossRef H. Yang, and D.P. Chu, "Phase flicker optimisation in digital liquid crystal on silicon devices", Opt. Express 27, 24556 (2019). CrossRef P. Bach-Y-Rita, et al. "Seeing with the Brain", Int. J. Hum. -Comput. Interact 15, 285 (2003). CrossRef Y. Tong, M. Pivnenko, and D. Chu, "Improvements of phase linearity and phase flicker of phase-only LCoS devices for holographic applications", Appl. Opt. 58, G248 (2019). CrossRef Y. Tong, M. Pivnenko, and D. Chu, "Implementation of 10-Bit Phase Modulation for Phase-Only LCOS Devices Using Deep Learning", Adv. Dev. & Instr. 1, 10 (2020). CrossRef H. Yang, and D. Chu, "Phase flicker optimisation in digital liquid crystal on silicon devices", Opt. Express 27, 24556 (2019). CrossRef J. García-Márquez, et al. "Mueller-Stokes characterization and optimization of a liquid crystal on silicon display showing depolarization", Opt.Express 16, 8431 (2008). CrossRef